Assessment of connectivity patterns of the marbled crab Pachygrapsus marmoratus in the Adriatic and Ionian seas through combination of genetic data and Lagrangian simulations - Marino, Ilaria Anna Maria; Schiavina, Marcello; Aglieri, Giorgio; Bevilacqua, Stanislao; Boscari, Elisa; Congiu, Leonardo; Faggion, Sara; Kruschel, Claudia; Papetti, Chiara; Patarnello, Tomaso; Paterno, Marta; Voutsinas, Emanuela; et al. (Frontiers in Marine Science, 2022)
Seascape connectivity studies, informing the level of exchange of individuals between populations, can provide extremely valuable data for marine population biology and conservation strategy definition. Here we used a multidisciplinary approach to investigate the connectivity of the marbled crab (Pachygrapsus marmoratus), a high dispersal species, in the Adriatic and Ionian basins. A combination of genetic analyses (based on 15 microsatellites screened in 314 specimens), Lagrangian simulations (obtained with a biophysical model of larval dispersal) and individual-based forward-time simulations (incorporating species-specific fecundity and a wide range of population sizes) disclosed the realized and potential connectivity among eight different locations, including existing or planned Marine Protected Areas (MPAs). Overall, data indicated a general genetic homogeneity, after removing a single outlier locus potentially under directional selection. Lagrangian simulations showed that direct connections potentially exist between several sites, but most sites did not exchange larvae. Forward-time simulations indicated that a few generations of drift would produce detectable genetic differentiation in case of complete isolation as well as when considering the direct connections predicted by Lagrangian simulations.Overall, our results suggest that the observed genetic homogeneity reflects a high level of realized connectivity among sites, which might result from a regional metapopulation dynamics, rather than from direct exchange among populations of the existing or planned MPAs. Thus, in the Adriatic and Ionian basins, connectivity might be critically dependent on unsampled, unprotected, populations, even in species with very high dispersal potential like the marbled crab. Our study pointed out the pitfalls of using wide-dispersing species with broad habitat availability when assessing genetic connectivity among MPAs or areas deserving protection and prompts for the careful consideration of appropriate dispersing features, habitat suitability, reproductive timing and duration in the selection of informative species.